Underestimation of Atypical Lobular Hyperplasia and Lobular Carcinoma in Situ at Stereotaxic 11-Gauge Vacuum-Assisted Breast Biopsy. (September 2013) - Gatta, G.; Di Grezia, G.; Ancona, A.; Capodieci, M.; Coppolino, F.; Rossi, C.; Feragalli, B.; Iacomino, A.; Cappabianca, S.; Grassi, R.
The aims of this study are to determine the frequency of diagnosis of atypical lobular hyperplasia (ALH) and lobular carcinoma in situ (LCIS) at stereotaxic-guided 11-gauge vacuum-assisted breast biopsy (VABB) and to assess the rate of underestimation of these at subsequent surgical excision and follow-up. Moreover, we aimed to define clinical, radiological and histological features of nonpalpable lesions in core biopsies that predict the lesion upgrade. Retrospective review of 11-gauge VABB was performed to identify the underestimation rate of nonpalpable lesions diagnosed as ALH or LCIS at VABB. Thirteen cases of ALH and 36 cases of LCIS were sent to surgery, 29 cases of ALH and 14 cases of LCIS were sent to follow-up. The clinical, mammographic and histologic features were assessed. The correlation between mammographic BI-RADS score and histological B-classification for both ALH and LCIS lesions were performed by Pearson's test. Of 1, 765 patients enrolled, lobular lesions (ALH and/or LCIS) occurred in 82 cases, and underestimation arose in 9 (10.9%). Two cases of underestimated ALH were upgraded to invasive lobular carcinoma and one to invasive ductal carcinoma. One case of underestimated LCIS was upgraded to ductal carcinoma in situ, two to invasive ductal carcinoma and three to invasive lobular carcinoma. The histology of the core and surgical specimens were compared. A significant difference was seen in the BI-RADS score (4–5 in 91% of underestimated lesions), and the size of the lesions (≥ 1.5 cm) for underestimated cases versus accurately diagnosed cases (p<0.001). Further significant parameters predictive for malignancy were the incomplete lesion removal by VABB and the presence of associated different breast lesions in the specimen. In conclusion, as far as ALH is concerned, we propose surgery as first choice when at least one of the following condition is respected: positive history for breast carcinoma, lesion >1.5cm, co-presence of high-risk lesions in the sample, signs of ductal involvement, high histological grading for atypia and follow-up in the other cases. Surgery is recommended in all cases of LCIS: